Pharmacy worker as a factor affecting reproductive female health - O. V. Filippova; N. V. Pyatigorskaya (Акушерство, гинекология и репродукция, 2020)
Aim: to assess a role of pharmacy workers in maintaining women's reproductive health.Materials and Methods. There were involved 150 pharmacy workers advising patients directly and selling them drugs and pharmacy product range, who answered the questionnaire about cause and rate of patient visits to the pharmacy for advice in various situations related to women's health. Some of such questions were devoted to choice factors in selecting recommended product. The survey was conducted anonymously.Results. Most often (92.0 %), respondents advise female patients with vulvovaginal candidiasis at least once a week. In addition, pharmacy workers respond to complaints related to menopause, premenstrual syndrome, and contraception: 50-70 % of respondents deal with similar requests at least once a week. Women also visit pharmacy requesting to recommend treatment for dysmenorrhea and mastopathy as well as agents preventing uterine fibroids. Quite rarely, visitors asked pharmacy workers for advice while planning a desired pregnancy: 30.7 % of the first-responders indicated that they did not consult such patients. Drug efficiency was the most prominent factor for 88.0 % of respondents in choosing the recommended product, whereas drug safety held the second place among 70.0 % responders. Most commonly pharmacy workers assess properties of drugs based on own personal experience (88.7 % of respondents).Conclusion. Women often turn to the pharmacy for help beyond pharmacy worker expertise. Improving the knowledge of pharmacy workers in the field of obstetrics and gynecology is a necessary socially-significant task.